Cytotoxic activity of bimetallic Ag@Se green synthesized nanoparticles using Jerusalem Thorn (Parkinsonia aculeata) - Hassanin, Hanaa A.; Taha, Amel; Ibrahim, Hairul-Islam Mohamed; Ahmed, Emad A.; Mohamed, Hisham; Ahmed, Hoda (Frontiers in Chemistry, 2024)
The process of green synthesis of metal nanoparticles is considered to be an eco-friendly path and cost-effective. In this study, bimetallic Ag@Se-P and Ag@Se-S nanoparticles were synthesized successfully using Parkinsonia aculeata aerial parts and seeds extract. The phytochemical contents in the P. aculeata aerial parts and seeds aqueous extract works as the reducing and stabilization capping agents without needs of any chemical stabilization additive for the bimetallic nanoparticles’ synthesis. The obtained results from UV-vis spectrophotometer, scanning electron microscope (SEM), X-ray powder diffraction (XRD), Energy-dispersive X-ray (EDS), Transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR) confirmed the successful synthesis of bimetallic nanoparticles with cluster irregular spherical morphology and crystalline nature and average particle size of 17.65 and 24.36 nm for Ag@Se-S and Ag@Se-P, respectively. The cytotoxicity assessment of greenly synthesized nanomatrials using seed extract and plant extract showed cell inhibition > 50 µg/mL. Ag@Se-S and Ag@Se-P, seed and plant extract significantly reduced the LPS induced inflammation and it was assessed by NO and cytokine IL-1β, IL-6 and TNF-α. mRNA and protein expression of PI3K and NFKB were significantly overexpressed in LPS induced RAW264.7 cell lines. Ag@Se-S and Ag@Se-P were downregulated the PI3K and NFKB in LPS induced cell models.